Association between high sensitivity C-reactive protein (hs-CRP) levels and the risk of major adverse cardiovascular events (MACE) and/or microembolic signals after carotid angioplasty and stenting - Farzaneh Foroughinia; Amir Ashkan Tabibi; Hanie Javanmardi; Anahid Safari; Afshin Borhani-Haghighi (Babol University of Medical Sciences, 2019)
Background: To evaluate the association between pre/post-procedural high sensitive C-reactive protein (hs-CRP) level and hs-CRP difference, and the risk of major adverse cardiovascular events (MACE) or new diffusion-weighted MRI lesions after carotid angioplasty and stenting (CAS). Methods: In this study, conducted in 2016 in Shiraz (Iran), patients who underwent diagnostic angiography and CAS were recruited. CAS was performed with distal embolic protection device on patients with both standard and high risk of endarterectomy. Pre/post-procedural hs-CRP, and hs-CRP difference were determined by immunoenzymometric assay method. Results: A total of 50 patients with diagnostic angiography and 60 patients with CAS were enrolled. No death, myocardial infarction, ischemic or hemorrhagic stroke, and need to revascularization occurred during the 30-days of the post-procedural period. Accordingly, the statistical evaluation in associating MACE and hs-CRP levels was impossible. Angioplasty was associated with higher frequency of elevated post-procedural hs-CRP in comparison to angiography (P=0.003). The higher age, symptomatic lesions, negative history of hypertension, and hs-CRP difference had significant association with the presence of new DWI lesions in univariate analysis (all P<0.05). Angioplasty of left carotid bulb and post-procedural hs-CRP levels was very close to the level of significance (P=0.06). But only left sided lesions had positive association (P=0.037) and hypertension had negative association (P=0.037) in multivariate regression analysis. There were significant association between post-procedural hs-CRP level (P=0.02) and hs-CRP difference (P=0.003), and the number of new lesions; and the hs-CRP difference and the accumulated lesion surface area (P=0.009). Conclusion: Post-procedural hs-CRP and hs-CRP difference may predict embolic complications of CAS.